Tax education and tax compliance: A multi-ethnic analysis - Hidayati, Berlina; Hermanto, Febrika Yogie; Nnamdi, Anthony Ogbolu (JIFA (Journal of Islamic Finance and Accounting), 2023)
For an emerging economy such as Indonesia, income taxes significantly contribute to her revenue generation profile. The efficacy of tax education during taxpayers' educational trajectory stands as a pivotal factor in achieving successful tax revenue collection. The primary objective of this study is to examine the impact of tax education on tax compliance among students from diverse ethnic backgrounds. This is a descriptive study with a quantitative approach. Open-ended questionnaires were developed, tested, and distributed to students. A total of 372 valid responses were returned and the data was analyzed using the Smart PLS tool. Findings from the analysis revealed a significant effect of tax education on tax compliance across all ethnic groups (Javanese, Sundanese, Batak, Minang, Malay, and Others) with the maximum and minimum effect recorded in the Sundanese (73.5%) and Batak (47.2%) respectively. This study contributes to bridging the research gap in tax education and tax compliance from a multi-ethnic approach in Indonesia. It is recommended that public tax awareness campaigns, targeted at both students and the public in Indonesia be sustained, as this drives an increase in tax compliance across all ethnicities in the medium to long term. This research makes a theoretical contribution by highlighting the significance of tax education as a determining factor. From a policy perspective, this study offers valuable insights to education policymakers, emphasizing the necessity for regular enhancements and adaptations in tax education practices.